Health and Nutrition Counseling for Children in Daycare Centers in Plantation Areas of Berau District - Binsa, Ucik Hidayah; Wahidah, Anita Solihatul; Khumaidah, Umi Karomatul (LPPM STAI Darul Falah, 2026)
This community service program in the operational area of PT Sentosa Kalimantan Jaya, Tanjung Batu Village, Pulau Derawan Subdistrict, Berau Regency, was driven by the persistent risk of nutritional and health problems among children in daycare centers due to limited knowledge, attitudes, and practices of caregivers and parents regarding balanced nutrition. The program aimed to enhance community capacity through nutrition and health education based on Participatory Action Research (PAR), engaging caregivers, parents, and local health volunteers in all stages. The implementation method included needs assessment, collaborative planning, interactive material delivery, hands-on practice, and evaluation using pre-post tests and reflective discussions. The results indicated a significant improvement in nutrition knowledge scores, awareness of healthy food choices, and better child feeding practices. These changes were reinforced by active participation and social support developed throughout the program, fostering a sense of ownership over the intervention. This success suggests that participatory approaches adapted to local contexts can produce relevant and sustainable outcomes, with potential for replication in other plantation-based communities with similar characteristics.